All new bathroom ideas that work - Schiff, David, 1955- (Taunton Press, Inc., 2018)
"Bathroom remodeling continues to top the list of the most common remodeling projects. All New Bathroom Ideas that Work contains essential information on all aspects of a bathroom update or complete remodel, from fixtures to lighting and cabinetry to flooring, so homeowners can make smart choices about what they want and can afford"--